Influence of viscosity on the shape of an air taylor bubble in a stagnant liquid under turbulent condition in falling film - Lertnuwat, Boonchai (Zielona Góra: Uniwersytet Zielonogórski)
This work aims to find the influence of the liquid viscosity on the shape of an air Taylor bubble, rising up in a pipe column which contains the liquid under conditions that the liquid is stagnant and the Froude number is approximately equal to 0.35. Five liquid viscosities (from 0.001 to 0.01 P . s) were selected for being computationally investigated. An appropriate shape of a Taylor bubble, corresponding to each selected viscosity, was obtained by considering a pressure distribution of the air inside the bubble. Simulation results showed that the Taylor bubble shape would be thicker if the liquid viscosity was decreased. This could be explained by using the theory of the log-law velocity profile.
Keywords: Dumitrescu`s model; viscosity; Taylor bubble; turbulence